Role of microbial inoculants on performance of rock phosphate in aerobic rice (Oryza sativa) - Yadav, Devideen; Singh, Y.V.; Yadav, Komal (Annals of Agricultural Research, 2017)
Performance of rock phosphate (RP) inoculated with phosphorus solubilising bacteria (PSB) and arbuscular mycorrizal fungi (AMF) was evaluated in terms of water productivity, biological health and available nutritional status of soil under aerobic rice (Oryza sativa L.) at ICAR- Indian Agricultural Research Institute (IARI), New Delhi, during Kharif-2013. Results revealed that application of RP inoculated with PSB and AMF enhanced irrigation water productivity by 16.1%, dehydrogenase activity (DHA) by 54.9%, alkaline phosphatase activity (APA) by 18.9% and microbial biomass carbon (MBC) by 64.3% over sole RP with same rate of application. Available nitrogen (N), phosphorus (P) and potassium (K) status of soil were also improved by applying 30 kg P through RP inoculated with PSB and AMF over 30 kg P through sole RP.